2017
DOI: 10.1111/ans.13873
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes for duodenal adenoma and adenocarcinoma: a multicentre study in Australia and the United Kingdom

Abstract: Due to the soft pancreatic texture and small pancreatic duct, pancreatic resection for NADTs is associated with a high rate of POPF which contributes to reduced survival. Nevertheless, surgery is associated with favourable 5-year survival compared to pancreatic resection for pancreatic adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
6
19
0
1
Order By: Relevance
“…There were only two (4%) post-operative deaths both due to myocardial infarction. The morbidity rate of 47% is similar to those published in previous studies of approximately 40–46% [5, 12, 13, 22, 23]. The majority (70%) of complications were Clavien-Dindo grade II requiring only medical intervention.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…There were only two (4%) post-operative deaths both due to myocardial infarction. The morbidity rate of 47% is similar to those published in previous studies of approximately 40–46% [5, 12, 13, 22, 23]. The majority (70%) of complications were Clavien-Dindo grade II requiring only medical intervention.…”
Section: Discussionsupporting
confidence: 84%
“…The proportion of patients with a pancreatic leak was 11%, in keeping with a published range of 9.3–28.9% [5, 12, 13, 21, 22]. The delayed gastric emptying rate of 6% is lower than the reported rates of 12.5–24% [5, 12, 13, 22, 23].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…SNADETs are reported to be detected in less than 0.4% of patients who undergo EGD [ 24 , 25 ], but recently, they have been detected more frequently because of advances in endoscopy [ 1 •]. Advanced duodenal cancer has a poor prognosis, and surgical treatment is associated with a high rate of morbidity and mortality [ 26 28 ]. Goda et al [ 1 •] reported that the rate of lymph node metastasis in early duodenal cancers was 0% in intramucosal cancers and 10% in submucosal cancers.…”
Section: Clinical Features Of Snadetsmentioning
confidence: 99%
“…Detection and treatment of SNADETs at an early stage is essential for good prognosis because of the poor prognosis of advanced duodenal carcinomas[ 14 , 15 ]. Conventionally, these lesions were removed surgically, but this procedure was associated with a high rate of morbidity and mortality[ 16 - 18 ]. Recently, endoscopic resections (ER) have been conducted for neoplasms in other organs including the esophagus, stomach, and colon, and ER appears to be an ideal treatment alternative to surgical resection for patients with SNADETs.…”
Section: Introductionmentioning
confidence: 99%